دور الطاقة المتجددة في تعزيز التنمية المستدامة - مشروع ديزرتيك - الأورو متوسطي أنموذجا - - بالي, مصعب; غفصي, توفيق; شليق, عبد الجليل (جامعة الوادي - University of Eloued, 2019)
تهدف هذه الدراسة لإبراز دور الطاقة المتجددة في تعزيز التنمية المستدامة، إذ أصبحت الطاقة عنصرا ضروريا وحيويا لا غنى عنه في عملية التنمية، فمع استمرار تزايد الطلب العالمي ودرجة الاعتمادية نتيجة التطور الاقتصادي والتكنولوجي والنمو الديمغرافي المتسارع لسكان الأرض، ومع إدراك محدودية المصادر التقليدية للطاقة وإمكانية نضوبها، دون إغفال الأضرار البيئية والمناخية الناجمة عن استخدامها، أصبح التوجه نحو المصادر المتجددة للطاقة أمرا ضروريا بهدف المساهمة بإيجابية في تحقيق مفهوم التنمية المستدامة بمختلف أبعادها، ليأتي " مشروع ديزرتيك " الجريء والعملاق كأحد أهم أشكال التعاون والتكامل الدولي بين ضفتي المتوسط عبر تقاسم الاستغلال المشترك للإمكانيات والموارد. الأحفورة، الطاقة المتجددة، مشروع دیزرتك. Abstract: The aim of this study is to highlight the role of renewable energy in promoting sustainable development. Energy has become an indispensable and vital element in the development process. As global demand and reliability continue to increase as a result of economic and technological development and the rapid demographic growth of the Earth's population, and recognizing the limitations of traditional energy sources and their depletion, Without ignoring the environmental and climatic damages resulting from their use. The drive towards renewable sources of energy has become necessary in order to contribute positively to the realization of the concept of sustainable development in all its dimensions. The bold and gigantic Desertec project is one of the most important forms of international cooperation and integration between the two shores of the Medite
The role of renewable energy in promoting sustainable development - Euro-Mediterranean Desertec project as a mod
مقال
Keywords: الدول الأورو متوسطية، التنمية المستدامة، الطاقة الأحفورية، الطاقة المتجددة، مشروع ديزرتيك.